Hypertrophic scar outcomes in fractional laser monotherapy versus fractional laser-assisted topical corticosteroid delivery: A randomized clinical trial - Woraphong Manuskiatti (2022)
Topical corticosteroid delivery following fractional laser treatment is an effective means of treating hypertrophic scars. However, the relative efficacy of adjuvant corticosteroid treatment vs fractional laser monotherapy alone is unclear. The aim of this study was to compare the efficacy and safety of fractional laser-assisted topical corticosteroid delivery with fractional laser monotherapy in the treatment of hypertrophic scars. In this randomized, comparative, split-scar trial of 19 subjects, a borderline significant reduction in scar thickness was observed at 3-month follow-up in the laser+steroid group compared with laser+petrolatum (p = 0.049). However, no significant long-term difference in scar flattening was observed between the 2 groups. Patient and Observer Scar Assessment Scale scores showed significant improvement in scar appearance from baseline without significant differences between treatment groups. In conclusion, fractional laser monotherapy is an effective treatment for hypertrophic scars, and the application of topical corticosteroid provides no long-term synergistic effect to fractional laser monotherapy.